2008
DOI: 10.1177/1049909108318569
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Place for Sexuality in the Holistic Care of Patients in the Palliative Care Phase of Life?

Abstract: Being diagnosed with a life-limiting condition is a traumatic event. The journey to the moment of death is usually only done once--so it is a time of fears and uncertainty. Sexuality is particularly vulnerable at this time. It may be difficult for both patient and partner to deal with the changes in sexuality without professional assistance. It is "sexuality" rather than "sex" that defines the meaningful relationships people have with themselves and significant others. When sexuality is lost or changed, import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
0
36
0
2
Order By: Relevance
“…Health professionals do not address the sexual concerns because of fears of being intrusive, personal discomfort, inadequate knowledge, time constraints, and poor confidence with intimate communication [37]. The discomfort of health professionals in addressing sexuality in advanced cancer patients is confirmed by the finding that only one out of ten patients in a palliative care setting had been asked about their sexuality [38].…”
Section: C) Barriers In Advanced Cancer Populationmentioning
confidence: 58%
See 1 more Smart Citation
“…Health professionals do not address the sexual concerns because of fears of being intrusive, personal discomfort, inadequate knowledge, time constraints, and poor confidence with intimate communication [37]. The discomfort of health professionals in addressing sexuality in advanced cancer patients is confirmed by the finding that only one out of ten patients in a palliative care setting had been asked about their sexuality [38].…”
Section: C) Barriers In Advanced Cancer Populationmentioning
confidence: 58%
“…However, most patients are willing to talk about their sex lives and the impact of the disease on their sexual function [39]. Sexuality continues to be important at the end of life, although it is often emotional connection to others that is more important than the physical expression [37]. Thus, within the patient's ability to function and desire for it, sexuality should be acknowledged and included in the holistic patient management.…”
Section: C) Barriers In Advanced Cancer Populationmentioning
confidence: 98%
“…As postulated by Redelman (2008), sexuality does not necessarily mean the conflation of male and female genitals but it also includes friendship, cuddling, masturbation, vaginal selfstimulation, relaxation, touching and kissing (Madunagu, 2007;Redelman, 2008). However, prevalent within the family of contextual heteronormative practices is the sub-theme of reproduction and motherhood, which I discuss below.…”
Section: Enhancing Eroticism Through Use Of Vaginal Productsmentioning
confidence: 99%
“…Although it has been reported that patients had found it appropriate to discuss their sexual concerns with nurses [2][3][4], this was rarely included in their interactions with their patients. Several perceived barriers during health care professional-patient interactions have been reported such as lack of knowledge and difficulty with the concept of including sexuality within holistic care [5]; boundary issues with fears of causing offense, seeming intrusive or inappropriate; personal discomfort, anxiety and inappropriate skills to address such issues especially with its multitude of variations; and time/privacy constraints [6].…”
Section: Introductionmentioning
confidence: 99%
“…As part of this holistic care, nurses and other health care providers are often required to help people [2][3][4][5][6][7] overcome problems related to sexual matters. They may be faced with questions about family planning, fertility regulation methods and pregnancy and concerns about sexual functioning.…”
Section: Introductionmentioning
confidence: 99%